How green is my industry? The case of Turkey - Aksoy, Tolga; Gonel, Feride (EMERALD GROUP PUBLISHING LTD, 2015)
Purpose - The purpose of this paper is to give a good overview of the relationship between industrial growth and industrial pollution in Turkey. The question is to what extent dirty industries have been affected by the regulations on the control of environmental degradation. Design/methodology/approach - The approach for this study uses all regulations which serve for protecting human and its environment from danger arising from dirty industries in Turkey. After presenting brief explanations on green industry, next sessions explain and compare the situations of the Turkish dirty industries and its relationship with related regulations in the European Union (EU). Findings - The authors offer three solutions. First, clean consumption should be stimulated in Turkish society. Second, Turkish Government should conduct more joint projects with the EU. Third, EU funds should be directed to cleaner production technologies to subsidize dirty industries during the negotiation process. Originality/value - Green industry can be assessed as a steep road to build a sustainable future. For a long time, the unsustainability of current forms of industrial production has been discussed in Turkey. As a solution some argue that if governments support, industries can finance their own transformation more rapidly. However, these arguments do not mean that industries voluntarily accept these changes.
Keywords: Sustainable development; Industry; Science & Technology - Other Topics